2017
DOI: 10.1161/jaha.117.005831
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Carotid Artery High‐Risk Atherosclerotic Plaques in Chinese Patients With Cerebrovascular Symptoms: A Chinese Atherosclerosis Risk Evaluation II Study

Abstract: BackgroundCarotid atherosclerotic plaque rupture is an important source of ischemic stroke. However, the prevalence of high‐risk plaque (HRP) defined as plaques with luminal surface disruption, a lipid‐rich necrotic core occupying >40% of the wall, or intraplaque hemorrhage in Chinese population remains unclear. This study uses carotid magnetic resonance imaging (CMRI) to investigate HRP prevalence in carotid arteries of Chinese patients with cerebrovascular symptoms.Methods and ResultsPatients with cerebral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 46 publications
(73 reference statements)
1
55
1
Order By: Relevance
“…5,28 A recent cross-sectional study showed that 16.6% symptomatic carotid arteries had IPH. 21 We found the intracranial artery IPH in our study population was more prevalent than that in previous studies. Xu et al 5 reported that the intracranial artery IPH was detected in 15.8% symptomatic patients.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…5,28 A recent cross-sectional study showed that 16.6% symptomatic carotid arteries had IPH. 21 We found the intracranial artery IPH in our study population was more prevalent than that in previous studies. Xu et al 5 reported that the intracranial artery IPH was detected in 15.8% symptomatic patients.…”
Section: Discussioncontrasting
confidence: 48%
“…19 Investigators utilized twodimensional (2-D) MR vessel wall imaging to identify atherosclerotic plaques in symptomatic patients and found that the prevalence of carotid plaques was 66.7%. 20 Most recently, with 2-D MR vessel wall imaging, Zhao et al 21 found that more than 60% of carotid high-risk plaques developed lower grade stenosis (stenosis <50%). In carotid artery MR vessel wall imaging, traditional 2-D protocol only provides less than 40 mm of longitudinal coverage centered to the bifurcation and could not capture the plaques occurred in more distal or proximal arterial segments.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to our dominant recruitment of patients with mild stenosis (stenosis <50%). It has been proven that the prevalence of IPH will increase with severity of carotid artery stenosis …”
Section: Discussionmentioning
confidence: 99%
“…A simple linear measurement of the greatest plaque thickness can be a strong discriminator in identifying high-risk plaque (Fig 3), even better than the degree of stenosis. 48 Studies have shown that greater overall plaque thickness is associated with cerebrovascular ischemic symptoms, even in patients with strokes of an undetermined source. [48][49][50][51] While an exact threshold of total plaque thickness to determine increased plaque vulnerability has not been established, it may be in the 2.5to 3-mm thickness range.…”
Section: Relatively Higher Risk Featuresmentioning
confidence: 99%